An Exploratory Comparative Case Study of Employee Engagement in Christian Higher Education - Daniels, Jessica R. (Christian higher education, 2016)
Numerous studies have identified a positive correlation between employee engagement and overall organizational performance. However, research on employee engagement specifically within higher education is limited, and even less attention has been focused on engagement within the context of Christian higher education. An exploratory comparative case study research design was used to explore two faith-based universities that are atypical examples of excellence as measured by the Best Christian Workplace Institute (BCWI) "Employee Engagement and Organizational Culture" survey. Analysis of data gathered from 53 interviews with employees and document analysis led to the identification of institutional characteristics that fostered employee engagement at two universities that consistently exhibited high rankings of employee self-reported engagement based on the BCWI survey results. Despite substantial differences between the two institutions, commonalities were identified in many of the characteristics that fostered employee engagement on the two campuses. The findings revealed that the shared themes of mission, community, empowered human resource departments, and a sense of positive momentum all contributed to the atypically high employee engagement levels that resulted in a positive and empowering organizational culture.